The Efficacy of 0.5 Gram NaCl Capsule in the Treatment of Umbilical Granuloma in Neonates: A Case Report - Tubagus Ferdi Fadilah; Nafisa Salma Wulandari; Nia Nurul Aziza; Dita Setiati; Firda Fairuza; Nathalia Ningrum; Meiriani Sari (Jurnal Kedokteran Diponegoro)
Background: An umbilical granuloma is a common benign condition in neonates characterized by the overgrowth of granulation tissue at the base of the umbilicus following umbilical cord detachment. While the standard treatment involves the use of silver nitrate, with its associated risks and need for clinical visits, alternative treatments such as the application of sodium chloride (NaCl) capsules have gained attention for their efficacy, safety, and cost-effectiveness in home settings. Case Presentation: Herein, we present the case of a 3-week-old female infant diagnosed with an umbilical granuloma post umbilical cord detachment. The management involved the application of a 0.5 gram NaCl capsule directly to the granuloma, covered with sterile gauze, and repeated over several days. This approach resulted in a significant reduction in granuloma size and total resolution within two days, without the complications or irritation sometimes associated with silver nitrate. Parents reported ease of administration at home and high satisfaction levels due to the treatment's effectiveness and minimal need for healthcare visits. Conclusion: The use of a 0.5-gram NaCl capsule offers a valid and effective home-based treatment alternative for umbilical granuloma. It provides a practical option, especially where access to silver nitrate is limited, with the added benefits of ease of use and reduced medical costs. With proper parental education and adherence to the treatment protocol, NaCl can serve as a first-line or alternative therapy. Further large-scale studies are recommended to verify long-term effects and potential complications.